50-pound autoclave used for production of polymers (1946)
General view of a 50-pound autoclave first used for the production of "Fiber V," later branded as Dacron polyester fiber, at a DuPont semiworks facility. During production, a partially-evaporated salt solution was fed into the autoclave and heated under pressure in order to precipitate polymerization. Once polymerization occurred, additional water was bled off and the pressure was slowly reduced to atmospheric levels before the polymer was extruded.
Keywords: Textile fibers, Synthetic; Polymers; Polyester fibers; Autoclaves; Polyester fibers--Testing; E.I. du Pont de Nemours & Company; Machinery